Genomic and Agronomic Innovations for Enhancing Abiotic Stress Tolerance in Global Food Crops under Climate Change Scenarios - Muhammad Rafi (Agriculture Journal, 2024)
Climate change poses a significant threat to global food security by increasing the frequency and intensity of abiotic stresses such as drought, salinity, and extreme temperatures on major food crops. This study aimed to evaluate and integrate genomic and agronomic innovations to enhance abiotic stress tolerance in key global crops. A combination of laboratory and field experiments was conducted using diverse crop varieties, including wild relatives and genetically modified lines, under controlled abiotic stress conditions. Advanced phenotyping, next-generation sequencing, and CRISPR-Cas9 gene editing were employed to identify and validate candidate genes associated with stress tolerance. The results demonstrated that wild-derived and genome-edited varieties exhibited superior physiological performance and yield stability under stress compared to conventional cultivars. Key genes such as DREB2, AREB1, and AVP1 were identified as crucial regulators of stress response. Integrating adaptive agronomic practices with genomic innovations resulted in synergistic improvements, increasing yield by up to 25% under stress. These findings underscore the importance of a multidisciplinary approach for developing resilient crop varieties and sustaining food production under climate change. However, further research is needed to assess long-term ecological impacts and ensure broad adoption of these technologies.